Perkembangan Historis Konsep Hardship dan Implementasi Nilai-Nilainya di Indonesia - Mahesa Pangestu; Arief Suryono (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2026)
Contract law recognizes the concept of force majeure as a mechanism to address extraordinary circumstances that hinder the performance of obligations, namely unforeseen events beyond the debtor’s control that may result in the release or suspension of obligations. However, this concept has limitations, as it does not encompass situations such as economic or monetary crises. In the development of international contract law, the UNIDROIT Principles of International Commercial Contracts 2016 (UPICC) introduce the concept of hardship as a response to fundamental changes in circumstances that affect the economic equilibrium of the parties. Although hardship has not been explicitly recognized in Indonesian law, it is considered more relevant for addressing such conditions.This study aims to examine the historical development of the concept of hardship and to analyze the implementation of its underlying values in Indonesian legal practice. The method employed is normative legal research, utilizing primary, secondary, and tertiary legal materials. The findings indicate that, despite the absence of explicit regulation within the national legal system, the values of hardship have been reflected in several court decisions through approaches grounded in fairness and contractual adjustment.The implication of this study is that the concept of hardship has the potential to be explicitly adopted into Indonesian contract law in order to fill existing legal gaps and provide a more adaptive solution to changing circumstances, particularly in addressing economic or monetary crises that fall outside the scope of the force majeure regime